300 Efficacy of the measurements of the vaginal electrical resistance to determine the phase of the estrous cycle in lactating dairy cattle. (5th December 2019) - Maquivar, Martin G; Swain, John; Chiapetta, Hannah; Stumvoll, Tynnetta; Baker, Katelin; Marchesseault, Grace; Miller, Andrew; Friend, Michael; Connett, Marie; Patil, Parvati
Abstract: Estrus detection in dairy cattle is an important factor that contributes to the reproductive efficiency. Lack and inaccuracy of heat detection are associated with increased days open, calving interval, economic loss and culling due to infertility. Efforts have been made to identify methods to assist in estrus detection. The objective of this study was to examine if vaginal electrical resistance (VER) measured by a commercial probe throughout the estrous cycle in lactating dairy cows aids to determine the onset of estrus. A total of 9 lactating Holstein cows were monitored for 2 – 3 estrous cycles, ultrasonography of the ovary, blood sample for progesterone and VER was assessed every other day during the luteal phase (LUT) and every day during the follicular phase (FOL). A total of 339 VER measurements were collected, 66 during the FOL phase and 273 corresponded to the LUT phase. Mean VER differed (P < 0.001) between FOL (294.5 ± 51.3) and LUT (316.4 ± 46.2), similarly the progesterone concentration was different between the LUT and FOL phases (0.38 ± 0.24 ng/mL vs. 3.41 ± 2.08 ng/mL, respectively) (P < 0.001). No differences were observed between the vaginal temperature of cows in LUT (38.2 ± 0.4 C°) or FOL phase (38.3 ± 0.3 C°). Cervix diameter differed (P < 0.01) between FOL (35.9 ± 3.8 mm) and LUT (34.5 ± 3.4mm), VER has a significant relation (P < 0.001) with the diameter of the Corpus luteum (279.8 + 1.54 x Cervix diameter). Similarly, VER had a significant relationship (P = 0.03) with diameter of the dominant follicle at estrus (355.2 + -3.9 x follicle diameter). These findings suggest that VER changes according to the phase of the estrous cycle, VER decreased during sexual receptivity and increased during the luteal phase. VER may improve the accuracy to diagnose heat in dairy cows.